2021
DOI: 10.1111/den.14172
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of early and late mortality after the treatment for early gastric cancers

Abstract: Objectives Although many patients with early gastric cancers (EGCs) die of non‐gastric cancer‐related causes, the association of the risk categories of lymph node metastasis (LNM) with all‐cause mortality remains unclear. We aimed to clarify the predictors of early and late mortality, separately. Methods Patients with endoscopic resection or gastrectomy for EGCs between 2003 and 2017 were retrospectively enrolled. We analyzed predictors for early and late mortality, including risk categories of LNM, treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…One study by Ogata et al 71 found that the most important predictors of early and late mortality following gastrectomy were age, Eastern…”
Section: Author Year Countrymentioning
confidence: 99%
“…One study by Ogata et al 71 found that the most important predictors of early and late mortality following gastrectomy were age, Eastern…”
Section: Author Year Countrymentioning
confidence: 99%
“…This result can be interpreted as valid from the fact that in Japan, women have a longer life expectancy than men at same age 5 . Male sex has also been reported as a predictor of early mortality after ER for EGC 6 . Although there is a limitation due to the low number of events in women, the mortality was obviously higher in men (20.3% vs. 38.8%, respectively).…”
mentioning
confidence: 98%
“…In this issue of Digestive Endoscopy , Ogata et al . analyzed all‐cause mortalities after ER or surgery and investigated the predictors of early and late mortality 7 . Multivariate analysis revealed that the most important predictor for early and late mortality was age ≥85 years.…”
mentioning
confidence: 99%
“…Although both age ≥85 years and eCuraC‐2 (intermediate‐ and high‐risk LNM) were independent predictors of mortality, the hazard ratio (HR) was higher for patients aged ≥85 years (HR 2.88) than those for patients with eCuraC‐2, intermediate‐ and high‐risk LNM (HRs 2.12 and 1.85, respectively). Moreover, the HR was higher for patients with worse physical status indices than those for patients with eCuraC‐2, intermediate‐ and high‐risk LNM 7 . Thus, the treatment strategy can also be determined according to the patient’s comorbidities or physical status, since both gastric cancer‐related and unrelated causes contribute to mortality.…”
mentioning
confidence: 99%
See 1 more Smart Citation